ANALISIS PENGARUH KUALITAS PRODUK, PERSEPSI HARGA, DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE IPHONE DI KOTA SEMARANG - Amelia Rezky Nur Mutia, 14.05.51.0245; Setiawan, Mulyo Budi (Students' Journal of Economic and Management, 2018)
This research will analyze the effect of product quality, price perception and brand image on purchasing decision on iphone smartphone in Semarang city by taking 105 respondents. From the result of this research, there are negative and insignificant influe . nce between product quality to decision of iphone smartphone purchase in Semarang city. There is positive and insignificant influence between price perception to decision of iphone smartphone purchase in Semarang city, And There is positive and significant influence between brand image to decision to buy iphone smartphone in semarang city. Results are still limited in scope, so the conclusions of this study can not be generalized. Keywords: Product Quality, Price Perception, Brand Image, Purchase Decision.